Integrasi Semantik Terapan dan Pragmatik dalam Pembelajaran Bahasa Arab - Martunis; Azhar, Yusron el-Hariq; Ajironi; Hariyadi, Sidiq Tri; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study explores the integration of applied semantics and pragmatics in Arabic language learning within the framework of ilmu lughah tathbiqi (applied Arabic linguistics). Using a qualitative-descriptive method based on library research, this study analyzes how lexical, grammatical, and contextual meanings—when combined with pragmatic approaches—enhance learners’ communicative competence. The findings show that effective Arabic teaching should not only focus on grammar and vocabulary but also emphasize contextual and pragmatic aspects that reflect real communication. Applied semantics provides a theoretical foundation for understanding how meanings are constructed and interpreted, while pragmatics develops the ability to use language appropriately within social and cultural contexts. Integrating these aspects supports the formation of comprehensive linguistic, sociolinguistic, and pragmatic competence essential for authentic Arabic communication.